Asymmetric synthesis of γ-chiral borylalkanes via sequential reduction/hydroboration using a single copper catalyst. Issue 33 (17th August 2020) - Han, Jung Tae; Lee, Jin Yong; Yun, Jaesook
Abstract : Copper-catalyzed reductive hydroboration of γ, γ-disubstituted allylic substrates enables preparation of γ-chiral alkylboron compounds in a one-pot cascade manner. Abstract : The synthesis of γ-chiral borylalkanes through copper-catalyzed enantioselective SN 2′-reduction of γ, γ-disubstituted allylic substrates and subsequent hydroboration was reported. A copper–DTBM-Segphos catalyst produced a range of γ-chiral alkylboronates from easily accessible allylic acetate or benzoate with high enantioselectivities up to 99% ee. Furthermore, selective organic transformations of the resulting γ-chiral alkylboronates generated the corresponding γ-chiral alcohol, arene and amine compounds.